Bubble departure characteristics in a horizontal tube bundle under cross flow conditions. (March 2018) - Goel, Parul; Nayak, Arun K.; Das, Mihir K.; Joshi, Jyeshtharaj B.
Highlights: Experiments of nucleate boiling under pool and cross flow conditions. Observation of vapor bubble departure diameter (D) and frequency (f) for saturated water. Parametric study of departure diameter and frequency with heat flux, wall superheat and mass flux. Systematic study for the effect of presence of tube bundles on the bubble departure characteristics. New empirical correlations for departure diameter and frequency under pool and cross flow conditions. Abstract: The visualization experiments for measuring departure diameter and frequency of vapor bubbles in the saturated nucleate boiling of distilled water have been carried out at atmospheric pressure. The experiments were carried out for an isolated single cylindrical tube and that for a tube bundle under pool and cross flow boiling conditions. The test setup was a stainless steel cuboidal tank of dimensions 400 mm × 200 mm × 180 mm provided with a 5 × 3 staggered tube bundle with an equilateral triangular pitch of 1.95. The departure diameter and frequency were measured using a high-speed camera to understand the parametric behavior of the bubble departure characteristics in a tube bundle under pool and cross flow condition. The range of operating conditions was: (1) heat flux q ″ = 8 − 28 k W / m 2, (2) wall superheat Δ T s a t = 7 − 22 K, (3) inlet mass flux G = 120 − 303.5 kg / m 2 s . The departure diameter and frequency were found to increase with an increase in the heat flux, but decrease with an increase in the mass flow rate. The local departure diameter and frequency were observed to increase as the neighboring tubes in the bundle were successively heated. Empirical correlations have been developed for departure diameter and frequency for saturated nucleate boiling under cross flow conditions incorporating the effect of the tube bundle. The correlations were found to predict experimental data within acceptable limit.